SYNONYMOUS CONDON USAGE BIAS AND OVEREXPRESSION OF A SYNTHETIC xynB GENE FROM Aspergillus niger NL-1 IN Pichia pastoris - Fei Li, Shiyi Yang (BioResources, 2012)
To further improve the expression level of recombinant xylanase in Pichia pastoris, the xynB gene, encoding the mature peptide from Aspergillus niger NL-1, was designed and synthesized based on the synonymous condon bias of P. pastoris and optimized G+C content. 155 nucleotides were changed, and the GC content decreased from 57.7% to 43.6%. The synthetic xynB was inserted into the pPICZaA and then integrated into P. pastoris GS115. The activity of the recombinant xylanase reached 1414.7 U/mL, induced with 0.8% methanol after 14-day cultivation at a temperature of 28oC in shake flasks, which was 267% higher than that of the native gene. Furthermore, the maximum xylanase activity of 20424.2 U/mL was obtained by high-density fermentation in a 5-L fermenter, which was the highest xylanase expression in P. pastoris yet reported. The recombinant xylanase had its optimal activity at a pH of 5.0 and temperature of 50oC. The recombinant xylanase was stable over a pH range of 4.5 to 8.0. Thus, this report provides an industrial means to produce the recombinant xylanase in P. pastoris.